Migração climática e a poética da arte-educação-ambiental nas narrativas de moçambicanos - Soares, Cristiane Carolina de Almeida (2022)
The aim of this paper is to interpret the migratory flows, identifying the adaptation difficulties experienced by migrants from Mozambique, understanding these movements as consequence of global climate collapse. Denouncing climate catastrophes is part of our responsibility as educators. However, we believe that art can help the way of life, we want to understand whether the “living well” of Mozambicans includes art-environmental-education as poetics of its announcement. Through their narratives of struggle and resistance, the methodological paths were based on the Cartography of the Imaginary, proposed by Michèle Sato, under the phenomenology of Gaston Bachelard. Among the Bachelardian archetypes, we highlight water, precisely because it represents the element that has a deep relationship with these people, permeating their ways of life, dreams, difficulties, and their relationship with Nature. The phenomenological waters touch other elements, conferring their inseparability, tensioned or softened by these encounters. We support the thesis that art-environmental-education, inspired by the phenomenology of Michèle Sato and Gaston Bachelard, can be one of the ways to alleviate a little of pain caused by the ruins of climate collapse. By energizing voices, the trajectory of climate collapse is interpreted. Moving away from catastrophic fatalism, the narratives of migrants interpret culture and nature in a combined way, with days and nights complementing each other in the phenomenology of Bachelard and Sato. It is necessary for public policies to be able to hear the voices of sensitivity, emotions and art, so both laws and programs can transform the chaotic matter of the world into a pedagogy of hope.